HPB P34 Complexity alone is not an indication for resection of liver cysts. (7th December 2022) - Al-Khafaji, Nadeem; Abdalkoddus, Muhammad; Wong, Newton; Roach, Huw; Skipworth, James; van Laarhoven, Stijn; Abbadi, Reyad
Abstract: Background: Most cystic liver lesions are simple biliary cysts (SBC) and have no malignant potential. Surgical deroofing may be indicated if symptomatic. Mucinous cystic neoplasms (MCN) represent less than 5% of liver cysts but can progress to mucinous cystadenocarcinoma and therefore require formal liver resection. While an MCN would demonstrate complex features on imaging, SBC may have similar appearances following episodes of infection or bleeding. CT, MR and US scans therefore have low positive predictive value for MCN, and most complex cystic liver lesions represent SBC. As a result, the decision to resect a complex cyst can be difficult for both patients and clinicians. We aimed to review our practice. Methods: Patients treated surgically for cystic liver lesions in a tertiary Hepatobiliary (HPB) centre between 2016 and 2019 were identified. Data on preoperative imaging, patient demographics, histology and follow up were obtained retrospectively. Results: 18 patients were treated surgically for liver cysts. Cysts were solitary in 3/18 cases. Eight were classified as complex on preoperative radiology. Five (all were complex and one was solitary) underwent formal liver resection and the remaining 13 were deroofing procedures. Patients who underwent liver resection were significantly more likely to have an asymptomatic liver cyst (4/5 vs 0/13, chi Squared, p<0.01). None of the resected specimens represented MCN, and complex characteristics on imaging were attributed to episodes of bleeding or infection. 14/18 patients were followed up for a median of 9 months (range: 2–36) without major adverse events. Conclusions: Surgical risks of liver resection must be balanced against likelihood of future malignancy. Cyst complexity alone is not an indication for resection and selected cases can be fenestrated if there are no other features to strongly suggest MCN, such as being solitary or in the absence of history suggesting cyst haemorrhage or infection